Measuring Changes in Regional Competitiveness over Time. A Shift-Share Regression Exercise - Oliver Fritz; Gerhard Streicher (Austrian Institute of Economic Research (WIFO), 2005)
Regional development in Austria has long been characterized by an east-south-west divide with eastern and southern states trailing western states in terms of value added and employment growth. In the 1990's, however, growth in value added was higher in the south and east and in terms of employment western states were outperformed by southern states. Applying an extended version of a regression shift-share approach proposed by Toulemonde (2001) these regional growth differentials are explained by decomposing annual value added and employment growth into regional, sectoral and temporal components; subsequently region-idiosyncratic and structural growth determinants can be distinguished. The results show that regional growth differences are accompanied by similar differences in the level of regional competitiveness. They also point to the fact that regions suffering from structural disadvantages often perform better than regions characterized by structural advantages which may be interpreted as a catching up process. @Die wirtschaftliche Entwicklung der neun österreichischen Bundesländer war lange von einem Ost-West-Gefälle geprägt, (süd-)östliche Bundesländer wiesen geringere Wachstumsraten sowohl bei der Beschäftigung als auch bei der Wertschöpfung auf. In den 1990ern zeigte sich ein komplexeres Bild: die südlichen und östlichen Bundesländer wiesen höhere Wertschöpfungszuwächse auf, die südlichen Regionen zusätzlich auch höhere Beschäftigungsdynamik. Mithilfe eines erweiterten Shift-Share-Ansatzes (Toulemond 2001) wird eine Zerlegung der regionalen Wachstumsunterschiede in regionale, sektorale und temporale Komponenten versucht. Die Resultate zeigen, dass regionale Wachstumsunterschiede von Unterschieden in der regionalen Wettbewerbsfähigkeit begleitet werden. Interessanterweise zeigen strukturell benachteiligte Regionen oft eine erfreulichere Entwicklung; dies kann als Aufholungsprozess interpretiert werden.
Keywords: 330; Regionalentwicklung; Standortwettbewerb; Österreich